2020
DOI: 10.35829/econbank.v2i1.76
|View full text |Cite
|
Sign up to set email alerts
|

Determinan Kinerja Keuangan Perbankan Syariah Periode 2014-2018

Abstract: The increasing trend in the halal industry is one of the growth factors of sharia banking, but the increase in sharia banking growth is also accompanied by an increase in financing issued by sharia banks that can affect the financial performance of sharia banks. The high risk of financing and the weak fulfillment of the quality of Islamic bank human resources resulted in the performance of Islamic banks always below conventional banks. This study aims to determine the effect of intellectual capital, non-perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
1
1
4
Order By: Relevance
“…Dunnas et al (2020); Kurniawati et al (2020), Maqhfirah & Fadhlia (2020), also show that intellectual capital has a positive and significant effect on financial performance. In contrast to the research results of Arifulsyah & Nurulita (2020); Pangesti & Sutanto (2020); Yusra et al (2020), show that intellectual capital has no effect on financial performance. Nazra & Suazhari (2019), intellectual capital has a negative effect on company performance.…”
Section: Introductioncontrasting
confidence: 71%
“…Dunnas et al (2020); Kurniawati et al (2020), Maqhfirah & Fadhlia (2020), also show that intellectual capital has a positive and significant effect on financial performance. In contrast to the research results of Arifulsyah & Nurulita (2020); Pangesti & Sutanto (2020); Yusra et al (2020), show that intellectual capital has no effect on financial performance. Nazra & Suazhari (2019), intellectual capital has a negative effect on company performance.…”
Section: Introductioncontrasting
confidence: 71%
“…Trimulato (2018) concluded that there must be a form of IHR management to develop the competence of Islamic bank employees, one of which is through ZIKR, PIKR, and MIKR. Pangesti and Sutanto (2020) stated that one of the factors that cause low financial performance is the fulfillment of the quality of IHR of Islamic banks.…”
Section: Previous Researchmentioning
confidence: 99%
“…Penilaian terhadap kinerja keuangan yang terdapat pada perbankan syariah, dapat dilakukan dengan melihat tinggi rendahnya jumlah return on asset yang dimiliki. Dalam rasio ROA mengutamakan sebuah kekuatan yang dimiliki oleh perbankan syariah di dalam memperoleh sebuah keuntungan guna untuk melaksanakan operasional dengan memanfaatkan aset-aset yang dimiliki oleh perbankan syariah (Pangesti & Sutanto, 2020). Dalam surat edaran BI No.13/24/DPNP tahun 2021 menjelaskan bahwa kinerja keuangan pada perbankan dapat dikatakan memiliki nilai yang baik jika memiliki ROA diatas 1,5%.…”
Section: Pendahuluanunclassified